Organisation transformation in agile approach, a comparative analysis of IT and other sectors - Wojciech Idzikowski; Igor Perechuda (Institute of Economic Research (IER), 2017)
Research background: Last decades may undoubtedly be deemed as the period of exceptional transformation which has global dimension. One of its elements is the reorganisation of traditional ways of business management. Therefore, agile approach is more and more often one of the key aspects of building comparative advantage of a company. In this paper agile approach is understood as the capability of responding promptly to market's needs. Purpose of the article: The paper aims at presenting selected research findings concerning the description of agile approach usage in organisations. The main authors' objective is to present the way the transformation of organization is done or may be done with reference to agile approach. Methodology/methods: The paper comprises three parts. The first includes the results of analysis of literature concerning agile approach, where the authors make an attempt to answer the question: what are scientific studies in that regard? The literature analysis in that regard was conducted during academic internship at Shippensburg University, USA in 2016 and was based on the resources of its library. The second presents the findings of research done between 2005 and 2016 where case studies analyses of almost 50 companies in Poland and not only were conducted. In the last part of the paper, on the basis of the findings in the second part, the authors present a referencing process, which could in some cases increase the agility of organizational activities. Findings: The empirical studies show the differences in using selected agile activities for organizations from IT and other sectors. On this basis the last part of paper includes the referencing process, which in some cases could increase the agility of organizational activities. The authors are aware of the fact that the before mentioned referencing process is subject to quantitative verification which in turn will identify determinant of its usage; however, this is to be conducted in the next phase of research. In this phase the research of comparative-explorative nature as well as qualitative is presented.
Keywords: M31; M15; M10; 330; Marketing; Agile approach; Processes; IT; Strategic management